2005
DOI: 10.1191/1352458505ms1204oa
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to employment status changes in individuals with multiple sclerosis

Abstract: In a sample of 50 individuals with multiple sclerosis (MS), participants able to work full-time ('W'), those who reduced their hours ('CB') and those who were unemployed ('NW') were compared on demographic and disease variables and symptoms that the participants identified as being responsible for their work status change. The NW group had significantly greater physical disability than the other two groups and significantly more fatigue than the W group. The CB group had significantly more years of education a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
188
5
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(217 citation statements)
references
References 28 publications
14
188
5
10
Order By: Relevance
“…[5] Depression adversely affects functional status among patients with MS, such as increased time lost from work. [15] MS patients with depression experience disruption of their social support and family systems beyond what can be attributed to neurologic disease factors alone. There is also evidence that depression decreases adherence to treatment regimens for MS, and that adherence improves with treatment of depression.…”
Section: Impact Of Psychiatric Disorders On Msmentioning
confidence: 99%
“…[5] Depression adversely affects functional status among patients with MS, such as increased time lost from work. [15] MS patients with depression experience disruption of their social support and family systems beyond what can be attributed to neurologic disease factors alone. There is also evidence that depression decreases adherence to treatment regimens for MS, and that adherence improves with treatment of depression.…”
Section: Impact Of Psychiatric Disorders On Msmentioning
confidence: 99%
“…This finding may not be surprising given that people with higher levels of education tend to occupy positions that require less physical exertion, and the physiological effects of MS therefore may not impose work impediments to the extent that they do for those whose jobs require more physical exertion. Similarly, Smith and Arnett [20] reported that individuals with MS holding higher occupational statuses had the flexibility and, most probably, the authority to maintain employment by cutting back on their work duties and hours.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Typically, older minority group individuals with MS are less likely to be employed. Results are mixed regarding the impact of gender, with women with MS more likely to be unemployed than men in some studies but not in others [4,11,13,17]. Both men and women with MS are more likely to leave the work force if they have a spouse who is working [18].…”
Section: Demographic Factorsmentioning
confidence: 99%
“…The qualitative content mon reason for unemployment and early retirement 4 and often negatively affects activities of daily living, such as doing housework and attending social events. 5,6 Fatigue can be triggered by mental or physical exertion, but it can also occur without a trigger. 7 Although there are several theories of fatigue in MS, the causes of fatigue are still poorly understood.…”
Section: Patient Interviews/focus Groupmentioning
confidence: 99%